Influence of aluminum addition on the mechanical properties of brass/Al composites fabricated by stir casting - Alam, M.A. (Elsevier Ltd, 2021)
Brass has an interesting set of characteristics, such as good wear capabilities and high electrical and thermal conductivity. Aluminium has been utilized as reinforcement and matrix in the development of advanced composites. In the present investigation, the new unique material the brass/Al composite has been developed by liquid casting route. The effect of Al filler in varying wt. on the mechanical properties of new brass/Al composites were investigated. The tensile strength and hardness were evaluated for produced composites. The microstructural features were observed by optical microscopy. The optical microscopy revealed the uniform distribution of Al particles in the brass matrix. The tensile strength and hardness increased by increasing the Al contents. It was interestingly observed that the addition of 4 wt Al exhibits the uniform distribution of irregular block shape strengthening phase and has the best mechanical properties. The fine surface was obtained by addition of Al. This research work provides an advanced strategy for improving the overall characteristics of existing brass. Â© 2021 Elsevier Ltd. All rights reserved.